Opportunistic behavior in Malaysian public listed companies: the relationship between earnings management and management incentive / Mohd Tarmizi Ibrahim - Ibrahim, Mohd Tarmizi (2013)
This paper examines the relationship between earnings management and management incentive among public listed companies. The study uses a cross-sectional study where real activity manipulation on cash flow being used as proxy for earnings management. Data has been collected from 2010-2012 annual financial statements and DataStream of public listed companies in Malaysia. The study shows that earnings management techniques being used among the Malaysian public listed companies and its relationship with management incentive. Results indicate that management of Malaysian public listed companies use earnings management techniques in order to report positive performance of the company over the years. In addition to that result also shows that only free cash flow incentive has significant relationship with earnings management whereas the study fails to find any significant relationship between debt covenant and earnings management. Since there is little research on this area among Malaysian Public Listed Companies, this study will provide empirical evidence the use of earnings management and it relationship with management incentive.